Pre- and post-season visio-vestibular function in healthy adolescent athletes - Roby, P. R.; Metzger, K. B.; McDonald, C. C.; Corwin, D. J.; Huber, C. M.; Patton, D. A.; Margulies, S. S.; Grady, M. F.; Master, C. L.; Arbogast, K. B. (The Physician and Sportsmedicine, 2022)
Objective To evaluate pre - to post-season differences in individual subtests of the Visio-Vestibular Examination (VVE) in healthy middle and high school athletes.